Salcedo, Jorge Enrique, S. J. Las vicisitudes de los jesuitas en Colombia. Hacia una historia de la Compañía de Jesús, 1844-1861. Bogotá: Editorial Pontificia Universidad Javeriana, 2014. 356 pp. - Marín Leoz, Juana María (2014)
null